2012
DOI: 10.3748/wjg.v18.i45.6577
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the human epidermal growth factor receptor 2-phosphatidylinositol 3-kinase-v-Akt pathway in gastric cancer

Abstract: HER2 expression, PIK3CA mutations and EBV infection in gastric cancer were characterized. pAkt expression significantly correlates with HER2 expression and with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 36 publications
9
55
0
Order By: Relevance
“…Furthermore, in concordance with prior data [35,36], the study revealed a strong predilection for PIK3CA mutation in EBV positive tumors, with nonsilent PIK3CA mutations found in 80% of this subgroup (P < 0.001), that could be targeted using PI(3)-kinase inhibition.…”
Section: Molecular Classiication Of Gastric Cancers By "The Cancer Gesupporting
confidence: 71%
“…Furthermore, in concordance with prior data [35,36], the study revealed a strong predilection for PIK3CA mutation in EBV positive tumors, with nonsilent PIK3CA mutations found in 80% of this subgroup (P < 0.001), that could be targeted using PI(3)-kinase inhibition.…”
Section: Molecular Classiication Of Gastric Cancers By "The Cancer Gesupporting
confidence: 71%
“…Patients testing positive for the abnormal expression of the PI3K/AKT/mTOR pathway were more likely to be in the late stages of gastric cancer with a lower survival rate. [4][5][6][7] Several drugs targeting PI3K/AKT/mTOR pathways are currently in clinical trials for gastric cancer, including PI3K inhibitor (LY294002, MK2206), AKT inhibitor (MLN1117), and mTOR inhibitor (everolimus). [8][9][10][11] PI3K inhibitor and AKT inhibitor monotherapy showed promising effects in Phases I-II, while mTOR inhibitor failed to improve survival in the GRANITE-1 Stage III trial for advanced gastric cancer.…”
mentioning
confidence: 99%
“…A score 4 was considered to be positive. 4,5,7 statistical analysis Statistical Package for the Social Sciences (SPSS) version 16.0 (SPSS Inc., Chicago, IL, USA) was used for the statistical analysis. The correlation between PI3K, p-AKT, and p-mTOR expression and patient clinicopathologic factors was analyzed using the χ 2 test.…”
mentioning
confidence: 99%
“…Due to its important role in cancer, there is great interest in the development of inhibitors able to target on the signaling pathways in preclinical trials. Sukawa et al (19) detected the expression of p-Akt in the tissue specimens of 231 patients with gastric cancer, and identified that 53% gastric cancer tissue specimens exhibit p-Akt expression and that patients with p-Akt expression demonstrate poor prognoses. An additional previous study suggested that the expression of p-Akt in 45 gastric cancer tissue specimens was up to 82.2%, and associated with tumor growth and metastasis (20).…”
Section: Discussionmentioning
confidence: 99%